The Effect of E-Commerce Utilization and Tax Digitization on CV Citra Anggun Cosmetic's Performance During the Pandemic - geby, gabriella (PROCEEDING INTERNATIONAL BUSINESS AND ECONOMICS CONFERENCE (IBEC), 2022)
This study aims to determine the effect of the use of e-commerce and tax digitalization on the performance of CV Citra Anggun Cosmetics during the pandemic. The type of data used in this study is quantitative data, namely data obtained in the form of numbers. Source of data in the form of primary data. Primary data was obtained from the results of distributing questionnaires via google form to employees at CV Citra Anggun Cosmetics. The population in this study includes employees who work at CV Citra Anggun Cosmetics. The sample in this study uses a saturated sample, namely all employees who work in cv Citra Anggun Cosmetic. Data analysis and testing consisted of validity test, reliability test, descriptive statistics, classical assumption test, multiple regression analysis, partial hypothesis testing (t test) and simultaneously (F test) and coefficient of determination test. The results showed that E-commerce had no effect and was not partially significant on performance with a t-count value of 1.782 < 2.048, tax digitization had no partial effect on performance with a t-count value of 1.156 <2.048. E-commerce and tax digitization simultaneously have a significant effect on performance with an f table value of 7.514 > 3.35 and a coefficient value of 35.8%.